The Evolution of Sporting Consumption Habits among Socioeconomically Disadvantaged Children and Adults - Židek, Péter (Economica, 2024)
In the manuscript, grounded in secondary research, I present literature reviews and statistics outlining the benefits and constraining factors related to the engagement in sports among socioeconomically disadvantaged individuals. Sports serve as a highly effective tool for facilitating social integration and ensuring equal opportunities. It is crucial to examine the sporting consumption habits of the disadvantaged target group and identify inhibitory factors to assist decision-makers in supporting measures for promoting equal opportunities. To alleviate social disparities, it is essential to establish conditions that guarantee long-term participation for everyone in economic and social life. Recognizing and promptly addressing disadvantages that manifest early in life are key factors for success in later life. Providing support to needy children, expanding their opportunities, and reinforcing a comprehensive system of child protection and well-being are fundamental for their successful integration into society.